2019
DOI: 10.7759/cureus.6136
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Use of Routine Platelet Transfusions for Head Injured Patients on Antiplatelet Therapy

Abstract: Traumatic brain injury is responsible for over one million hospital visits, and thousands of deaths annually. The aging population is associated with an increased use of anticoagulation and antiplatelet agents which complicates traumatic brain injury. The use of antiplatelet agents significantly increases baseline risk of intracranial hemorrhage. However, routine platelet transfusion in an attempt to reverse the effects of antiplatelet agents may be detrimental. Here, we report a case of an elderly woman with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, platelet transfusions did not impact mortality of these TBI patients [142]. Platelet transfusion may seem to be an intuitive therapy for platelet dysfunction, but for TBI patients on antiplatelet agents, it is not effective at improving outcomes [146]. The large PATCH trial recently has demonstrated increased mortality in patients on antiplatelet agents who had TBI.…”
Section: Vet-guided Diagnosis and Treatment Of Platelet Dysfunction In Tbimentioning
confidence: 94%
See 1 more Smart Citation
“…However, platelet transfusions did not impact mortality of these TBI patients [142]. Platelet transfusion may seem to be an intuitive therapy for platelet dysfunction, but for TBI patients on antiplatelet agents, it is not effective at improving outcomes [146]. The large PATCH trial recently has demonstrated increased mortality in patients on antiplatelet agents who had TBI.…”
Section: Vet-guided Diagnosis and Treatment Of Platelet Dysfunction In Tbimentioning
confidence: 94%
“…These TEG-guided therapies enable physicians to quickly deliver focused therapies, accurately correcting coagulopathy while potentially conserving blood products. Still, there are heterogeneous and conflicting results regarding whether application of VETs like TEG ® correlate with improved patient outcomes and reduced mortality [1,39,40,84,86,123,129,140,141,[144][145][146]. Several studies exhibit improved survival when using a TEG-based resuscitation strategy compared to a CCA-guided treatment (PT, aPTT, fibrinogen, and D-dimer) [56,139,147].…”
Section: Treatment Of Ctbimentioning
confidence: 99%